Analisis Puisi “Pada Suatu Hari Nanti” Karya Sapardi Djoko Damono Dengan Pendekatan Struktural - Ayu Natasya; Dila Putri (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
The study of structuralism of poetry is a study of poetry that emphasizes the study of the building elements of the poem itself. In this case, a poem is considered as a unified whole. Therefore, the study of poetry with the theory of structuralism is an assessment that does not involve the poet's background and other factors that influence the creation of the poem. In the study of the poem "On One Day Later", using the descriptive method. the purpose of studying the poem "on a day" is to describe the use of language style. the poem "on a day later" means to express human feelings through experiences, thoughts, feelings, ideas, beliefs in the form of depictions of life that can evoke charm through the use of language and are described in the form writing.